The Fifth-Century Crisis*. (26th October 2017) - Smith, Christopher
Abstract: This essay seeks to establish the parameters of our uncertainty concerning one of the most difficult periods of Roman history, the period between the traditional end of the Roman monarchy and the passing of the Licinio-Sextian legislation. In addition to some methodological observations, the essay attempts to offer a model for understanding Roman choices and decisions in a period of change and transformation.